Constraints on visual exploration of youth football players during 11v11 match-play: The influence of playing role, pitch position and phase of play. Issue 6 (18th March 2020) - McGuckian, Thomas B.; Cole, Michael H.; Chalkley, Daniel; Jordet, Geir; Pepping, Gert-Jan
ABSTRACT: Visual exploratory action, in which football players turn their head to perceive their environment, improves prospective performance with the ball during match-play. This scanning action, however, is relevant for players throughout the entire match, as the information perceived through visual exploration is needed to guide movement around the pitch during both offensive and defensive play. This study aimed to understand how a player's on-pitch position, playing role and phase of play influenced the visual exploratory head movements of players during 11v11 match-play. Twenty-two competitive-elite youth footballers (M = 16.25 years) played a total of 1, 623 minutes (M = 73.8). Inertial measurement units, global positioning system units and notational analysis were used to quantify relevant variables. Analyses revealed that players explored more extensively when they were in possession of the ball, and less extensively during transition phases, as compared to team ball-possession and opposition ball-possession phases of play. Players explored most extensively when in the back third of the pitch, and least when they were in the middle third of the pitch. Playing role, pitch position and phase of play should be considered as constraints on visual exploratory actions when developing training situations aimed at improving the scanning actions of players.